SOME THERMOPHILIC FAGACEAE IN THE TERTIARY FLORA OF KRASKINO AND THE PROBLEM OF ITS AGE DETERMINATION - Pavlyutkin B.I. (My University, 2002)
The age problem of the fossil Tertiary flora of the Kraskino locality that corresponds to the Korean beds with Engelhardtia is discussed. The investigation of the fossil plants, collected by the author in the type locality of the flora of Kraskino type, led to the conclusion that it is similar to the subtropical flora in character and belongs to the Early Oligocene, in contrast to the widespread belief in the main climatic Miocene optimum as a time of the formation of this flora. Some thermophilic members of the family Fagaceae, including two new species, Castanea gracilis and Cyclobalanopsis paucinervis, are described.